Molecular phylogeny, structure modeling and in silico screening of putative inhibitors of aerolysin of Aeromonas hydrophila EUS112 - Yadav, Sunita Kumari; Panwar, Deepak; Singh, Ankita; Tellis, Meenakshi B.; Joshi, Rakesh Shamsunder; Dixit, Aparna (Journal of Biomolecular Structure & Dynamics, 2022)
Aeromonas hydrophila, a Gram-negative bacterium, causes diseases in fish, resulting in excessive loss to the aquaculture industry. Aeromonas is a highly heterogeneous group of bacteria, and the heterogeneity of the genus is attributed to variation and diversity in the virulence factors and toxins among various Aeromonas strains. One of the major toxins aerolysin, secreted by the bacterium, causes hemorrhagic-septicemia and diarrhea and can serve as a drug target. Here, we describe characterization, molecular phylogeny, and homology modeling of the aerolysin of A. hydrophila strain EUS112 (Ah(EUS112)) cloned in our lab. The encoded aerolysin is 485 amino acids long with an N-terminal signal sequence of 23 amino acids. Phylogenetic analysis of the aerolysin of Ah(EUS112) revealed that it belongs to a diverse group of toxins, showing maximum similarity with aerolysins of other Aeromonas strains followed by Vibrio toxin. The homology model of the mature aerolysin of Ah(EUS112) was generated using the crystal structure of a mutant aerolysin (PDB#3g4n) as the template, which showed that the encoded aerolysin exists as a channel protein. Validation of the generated model using bioinformatics tool confirmed it to be a good quality model that can be used for drug design. Molecular dock analysis revealed that drugs, aralia-saponin I, cyclamin, ardisiacrispin B, and aralia-saponin II bind to aerolysin with a higher affinity as compared to other drugs and at functionally important amino acids of aerolysin. Hence, these molecules can act as an effective therapeutics for inhibiting the aerolysin pore formation and curtail the severity of Aeromonas infection. Communicated by Ramaswamy H. Sarma
Keywords: Aerolysin; homology modeling; Molecular docking; Molecular dynamic simulation; phylogenetic tree